Quality of life of cervical cancer patient with support from nuclear family and extended family in Dr. Sardjito general hospital, Yogyakarta Indonesia: a comparative study - Pradjatmo, Heru; Nisman, Wenny Artanty; Fatmawati, Yayuk (International Journal of Research in Medical Sciences, 2017)
Background: Nature of the disease, side effect from treatments such as surgery, chemotherapy, and chemo radiation reduce the patient’s quality of life. Thus, the family support is substantial in cancer patient treatment. Aim of this study was comparing the quality of life of patients with cervical cancer in support of the nuclear family and extended family at Dr. Sardjito hospital Yogyakarta, Indonesia. Methods: The study population were all cervical cancer patients treated with chemotherapy in Dr. Sardjito general hospital, Yogyakarta, Indonesia from October to November 2016. Samples were collected using purposive sampling to obtain 62 respondents, 30 respondents for nuclear family group and 32 for extended family group. The study instruments were family support questionnaire, EORTC QLQ-C30 Indonesian version, and EORTC QLQ-C24 were translated to Indonesian. The quality of life was assessed during chemotherapy. Results: Quality of life for cervical cancer patient from supportive family had mean >50. The respective mean of general health status for patients from supportive nuclear and extended family were 76.28±21.434 and 67.82±22.017. Nearly all items in symptom, multi-item and single-item scales had mean <50, except item financial problem. Meanwhile, quality of life for cervical cancer patient from unsupportive family had mean >50. The respective mean of general health status for patients from unsupportive nuclear and extended family were 70.83±20.972 and 75.00±8.33. Nearly all items in symptom, multi-item and single-item scales had mean <50, except items fatigue and sore. Several items of quality of life had p<0.05, which were constipation (p=0.049), and financial problem (p=0.045). Conclusions: There was no significant difference between quality of life of cervical cancer patients with support from nuclear and extended families. However, in ‘financial problem’ item, nuclear family had better quality of life while in contrast, extended family had better quality of life in ‘constipation’ item. Family education program needed because several domains of quality of life is still low and requires family involvement in treatment.